High-throughput imaging of powdery mildew resistance of the winter wheat collection hosted at the German Federal ex situ Genebank for Agricultural and Horticultural Crops. (3rd March 2023) - Hinterberger, Valentin; Douchkov, Dimitar; Lueck, Stefanie; Reif, Jochen C; Schulthess, Albert W
Abstract: Background: Genebanks worldwide are transforming into biodigital resource centers, providing access not only to the plant material itself but also to its phenotypic and genotypic information. Adding information for relevant traits will help boost plant genetic resources' usage in breeding and research. Resistance traits are vital for adapting our agricultural systems to future challenges. Findings: Here we provide phenotypic data for the resistance against Blumeria graminis f. sp. tritici, the causal agent of wheat powdery mildew—a substantial risk to our agricultural production. Using a modern high-throughput phenotyping system, we infected and photographed a total of 113, 638 wheat leaves of 7, 320 winter wheat ( Triticum aestivum L.) plant genetic resources of the German Federal ex situ Genebank for Agricultural and Horticultural Crops and 154 commercial genotypes. We quantified the resistance reaction captured by images and provide them here, along with the raw images. Conclusion: This massive amount of phenotypic data, combined with already published genotypic data, also provides a valuable and unique training dataset for the development of novel genotype-based predictions as well as mapping methods.